Robert Ludlum's The Bourne Objective : Jason Bourne #8 - Lustbader, Eric; Ludlum, Robert, 1927-2001 (New York : Grand Central Pub., 2010)
Lustbader's cookie-cutter fifth Jason Bourne novel in the Ludlum franchise (after The Bourne Deception) downgrades the title character to a mere co-star with villain Leonid Arkadin, a graduate of the same covert training program, who also possesses almost superhuman combat skills. Bourne and Arkadin's globe-trotting pursuit of each other drives the main plot, which includes yet another secret cabal bent on world domination, Severus Domna. The members of Severus Domna have their eye on a ring Bourne possesses that's a clue to the location of King Solomon's legendary gold. Arkadin's use of silly aliases (e.g., Stanley Kowalski, Frank N. Stein) dissipates any effort at realism, while implausible and formulaic side stories involving Soraya Moore, ousted from her position with the CIA, don't help. Those who don't mind Bourne's devolution from the tortured amnesiac soul Ludlum created into a stock action hero will be most satisfied.
Keywords: Bourne, Jason (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Attempted assassination -- Fiction; Bombings -- Fiction; Aircraft accidents -- Fiction